As política de formação continuada de professores e sua relação com resultados do IDEB no ensino fundamental em Monção/ Maranhão - Almeida, Maria das Graças Amorim de (2017)
This research discusses the relationship of the teachers’ continuous education with the Education Development Index (IDEB) of the municipal education system of Monção city in the state of Maranhão, Brazil. This takes into account the Brazilian educational policy based on the preliminary external assessments of 1990s that propose the reform of the State, particularly in education. It aims to examine aspects of continuous education offered to teachers in the municipal public education system. Furthermore, it analyses what are the programs that promote the effectiveness of these trainings for professional development and their relationship with IDEB in the initial grades of basic education, from 2005 to 2015.The study articulates training experiences for teachers’ professional development in programs developed within the municipal education system, to students’ performance results from 2005 to 2015. Through methodological collection and analysis of official documents about programs developed by the Municipal Education Department of Monção city, the investigation examines data followed by bibliographic research, reviewing studies carried out on IDEB and on continuous teacher education correlating with data presented by INEP / MEC (Brazilian Ministry of Education). The theoretical framework on Continuous Education is drawn on Marcelo (1997, 1999); Imbernón (1994, 2011) and Marin (1995, 1998). The results of the analysis of continuous education courses show the existence of teacher education models aimed at a standard teacher’s training that would comply with established students’ assessment measures. These are standardized models that do not meet the particularities of each region, each school, and their teachers and students